Informed Application of the Standards on Support Surface Performance for Clinically Meaningful Use. (November 2020) - Sylvia, Cynthia; Gruccio, Paula; Jordan, Rosalyn; Morello, Susan Smith; Thurman, Kristen
ABSTRACT: BACKGROUND: The Support Surface Standards Initiative (S3I) has evolved with the goal of standardizing language and performance evaluation of support surfaces. There is a consumer need for education about support surface standards to transfer new information with clinical relevance. OBJECTIVE: To develop a framework for meaningful dialogue through consensus building that drives value-based purchasing, propose a clinically relevant path for understanding how to apply data from the standards into critical interprofessional analysis and support surface selection, and navigate the first tier of a process targeted as an educational initiative within the Standards Committee. METHODS: The authors purposively sampled the S3I Tissue Integrity Group with a semi-structured qualitative survey to identify the essential components of support surfaces standard performance testing. A two-phase interview and review process was implemented within the larger S3I group to achieve consensus on content for knowledge transfer, with a threshold of 80% agreement within the Standards Committee. RESULTS: Meaningful consensus was achieved on content associated with knowledge transfer of standards data. These standards will function as reliable benchmarks, enabling consumers to compare individual characteristics of one support surface to another. Product comparison will be based on the single characteristics of support surfaces and how those characteristics are relevant to the specific needs of the individual patient or patient populations, transferred in language that is meaningful to end users of the standards. CONCLUSIONS: The consensus process facilitated construction of a clinically relevant, interprofessional framework for the product selection process within the Standards Committee. It will enable the next tier of educational dissemination beyond the Standards Committee to a broader base of consumers to engage in value-based purchasing with enhanced understanding of support surface performance characteristics.